Transformasi Intelektual Islam Atas Dunia Barat - Taufik Afandi; Abdul Khobir (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines the influence of Islamic intellectual transformation on the development of Western civilization, especially in the transfer of knowledge, technology, and cultural values ​​from the Middle Ages to the modern era. The background of this study is based on the importance of understanding the contribution of Islamic civilization in building the intellectual foundation for the rise of Europe. This study aims to identify and analyze the contributions of Muslim scientists in various disciplines, such as philosophy, astronomy, mathematics, and medicine, and how these thoughts were adopted and developed in the Western world. The method used is a qualitative approach through historical literature studies and comparative analysis of classical and modern documents. The findings show that Islamic intellectual thought played a significant role in accelerating Western intellectual development, through translations of scientific works and the influence of the thoughts of figures such as Al-Farabi, Ibn Sina, and Ibn Rushd. The implications of this study emphasize the importance of recognizing the role of Islamic civilization in the history of global science, as well as the need to revitalize dialogue between civilizations to strengthen harmony and cross-cultural cooperation.